Analysis of Strategy Determination for Increasing the Competitiveness of the Active Pharmaceutical Ingridients Industry in Indonesia - Anwar Wahyudi; Iha Haryani Hatta; Shirly Kumala (Westscience Press, 2023)
The active pharmaceutical ingiridients industry is an infant industry in Indonesia. Efforts to carry out development have been made but have not been able to achieve the expected competitiveness so far. It is realized that competitiveness is an important part that can encourage the development of the active pharmaceutical ingiridients industry, so it is important to develop a useful strategy to develop the industry as expected. The formulation of the strategy is based on the statements of 16 experts who have experience in the pharmaceutical field in Indonesia. The analytical method used is descriptive qualitative analysis. The final results show that the government plays an important role in encouraging industrial development and increasing its competitiveness, so that it can ultimately encourage other industries.